Synthesis of D-Galactofuranose-containing molecules. Design of Galactofuranosyl acceptors - Marino, María Carla (2014)
D-Galactofuranose (D-Galf) is present in glycoconjugates of several pathogenic microorganisms but is absent in mammals, so it is a good target for the development of chemotherapeutic agents for the treatment of microbial infections. This fact has improved the interest in the synthesis of D-Galf-containing molecules for the corresponding glycobiological studies. The synthesis of oligosaccharides, glycoconjugates and mimetics of D-Galf requires specific methods for the preparation of galactose derivatives in the furanosic configuration, the synthesis of appropriate acceptors and efficient glycosylation methods for the construction of the alpha- and beta-D-Galf linkages. This review summarizes the different strategies developed for the preparation of partially protected derivatives of D-Galf, suitable as acceptors for the construction of (1,2), (1,3), (1,5) and (1,6) linkages, and describes recent applications.